Enzymatic preparation and identification of 5′-adenosyl-methylthiopropylamine for the impurity control in SAM fermentation. (December 2019) - Tang, Dandan; Shi, Feng; Yang, Xiuliang; Liu, Wei; Zhao, Weijun; Xian, Ruiqing; Huang, Lei; Cheng, Leming; Xu, Zhinan
Graphical abstract: Highlights: Decarboxylated S-adenosyl-L-methionine (SAM) was effectively biosynthesized in vitro . Pure decarboxylated SAM was prepared by semi-HPLC and identified by LC–MS. Prepared decarboxylated SAM was used for impurity control in SAM production. Abstract: S-adenosyl-L-methionine (SAM) is an important biosynthetic drug used for various diseases such as depression, arthritis syndromes and cirrhosis in clinical therapeutics. In order to ensure the high quality of SAM as a clinical drug, the key impurity, 5′-adenosyl-methylthiopropylamine (decarboxylated SAM, dC-SAM) should be monitored during the whole production process and in end tablet product. In the present work, the SPE2 gene encoding SAM decarboxylase was inserted into pET28a to obtain the expression plasmid pET28a- SPE2, which was transferred into Escherichia coli BL21 to construct the recombinant strain. With low temperature (26 °C) cultivation and 0.1 mM IPTG induction, the recombinant cells were collected to prepare cell lysates, which can be utilized to effectively prepare dC-SAM in vitro with the addition of SAM as the substrate. Then dC-SAM sample with high-purity (99.7%) was isolated from this biotransformation mixture by semi-preparative high performance liquid chromatography. Further, the molecular structure of the purified dC-SAM sample was confirmed by liquid chromatography-mass spectrometry. Finally, prepared dC-SAM was employed to detect the content of the impurity during one-month industrial SAM fermentation processes. Our work will be very helpful to the control of impurities during the whole production process of SAM and its end products.